Daya Dukung Ekosistem Mangrove Terhadap Hasil Tangkap Nelayan di Taman Hutan Raya Ngurah Rai, Bali - Lestari, Jero Ketut Tri Ayu; Karang, I Wayan Gede Astawa; Puspitha, Ni Luh Putu Ria (Journal of Marine and Aquatic Sciences; Vol 4 No 1 (2018), 2017)
Mangrove ecosystem is a complex ecosystem. The sustainability of fish resources is highly dependent on the sustainability of the mangrove ecosystem. The purpose of this research is to know the  mangrove density, fish catching from fisherman in mangrove area and relationship of mangrove vegetation and the quality of the waters with the fish catching in the mangrove. Data collections include mangrove condition, fish catching, and water environment parameter. Research conducted in the mangrove area Mina Werdhi Batulumbang (TP I) and Simbar Segara (TP II). The results of this study found 5 species of mangrove. The density values of species at research site I ranged between 0.02 ind / m 2 - 0.08 ind / m 2 . While the density value of species in this research site II ranged between 0.01 ind / m 2 - 0.07 ind / m 2 . Rhizophora mucronata type has the highest density. Fish catching is the largest average in research place I, that is 1.42 kg /day /fisherman with mangrove area 2,397 Ha and the research of site II shows that the fish production of fisherman catches of 0,8 kg / day / fisherman with mangrove area 1,986 Ha. There is a positive relationship between the density and area of mangrove with the number of fish catching, where the fish catching will increase when the mangrove area also increases and there is a strong relationship between the catch and dissolved oxygen.